'Quod grata lavacra nitescunt': Roman Villa Baths as Markers of Elite Competition in Continental North-Western Europe. (November 2021) - Maréchal, Sadi
Abstract : This article examines how villa baths in the north-western Roman empire can help us understand how rural regions were incorporated in the Roman cultural sphere despite the absence of cities and secondary agglomerations. Whereas in the first phase of Roman rule the addition of private baths to a villa could be interpreted as a marker of a Roman way of life, the ever larger and more luxurious bathhouses of the second and third centuries ad can only be understood in the context of intra-elite competition, revealing a real concern for displaying wealth and underlining social status, but also for leaving a family legacy. Here, a case-study in the rural north-west examines the role of baths in the self-representation of elites, the consolidation of elite peer interaction networks, the creation of social exclusion, and the inclusion of new ideas into local cultures.